KEKALAHAN PDI-P DALAM PEMILUKADA KABUPATEN KLUNGKUNG TAHUN 2013 - Pratama, Raenaldy Yoga; Bandiyah, Bandiyah; Erviantono, Tedi (Jurnal Nawala Politika, 2016)
ABSTRACT   Political parties is a means or a place for the community to achieve power in government. One political party in Indonesia is still showing its existence until now is the PDI-P. Bali province is one of the strong base PDI-P. The power of PDI-P not only be seen in the central government in Bali but also in all regency in Bali. Klungkung regency is one of districts in Bali that showed the dominance of PDI-P. It can be seen with the victory of PDI-P in local elections and legislative elections. But in 2013, PDI-P was defeat in Klungkung elections. The purpose of this study was to determine and describe the defeat causes of PDI-P in Klungkung regency election in 2013. The theory used is the Theory of Symbolic Interaction with the approach changes the meaning of a symbol of a political party. This research method is descriptive qualitative. The results of this study found that, PDI-P defeat in the election of 2013 was influenced by internal and external causes. The determining candidates late from DPP PDI-P, less solid political machine PDI-P that does not fully support the decision of the DPP PDI-P, and there are cadres are disappointed because it failed to become a candidate recommended by the DPP followed by supporters who ultimately did not choose PDI-P became the main cause of the internal side. In external side the ownership of cooperative from other candidates, incompatibility of candidates that determined PDIP with community's desire, and and the emergence of issues discrimination another candidate that gave rise to fanaticism of regionalism is a major cause of the external side. In this study concluded that Klungkung society is now more pragmatism in selecting candidates such as see figure and vision and mission that brought in compare the political party in the election. Klungkung society will impose his choice to candidates who give benefit from the social economy only. Keywords: Defeat, PDI-P, Symbolic Interaction